2016
DOI: 10.18632/oncotarget.7517
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-329 exerts tumor suppressor function through down-regulation of MET in non-small cell lung cancer

Abstract: MicroRNAs (miRNAs) act as key regulators of multiple cancers. Hsa-miR-329 (miR-329) functions as a tumor suppressor in some malignancies. However, its role on lung cancer remains poorly understood. In this study, we investigated the role of miR-329 on the development of lung cancer. The results indicated that miR-329 was decreased in primary lung cancer tissues compared with matched adjacent normal lung tissues and very low levels were found in a non-small cell lung cancer (NSCLC) cell lines. Ectopic expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Our results indicate that expression of MET receptor is also crucial for the proteolytic activity of melanoma cells—decreased digestion of fluorescently labelled gelatin and MMP‐9 activity were observed in melanoma cells with diminished level of this protein. Similar effect was observed by Sun et al who showed that MiR‐329 caused down‐regulation of MET expression what led to decreased mRNA level of MMP‐7 and MMP‐9 and thus reduced cellular migration and invasiveness of lung cancer cells.…”
Section: Discussionsupporting
confidence: 82%
“…Our results indicate that expression of MET receptor is also crucial for the proteolytic activity of melanoma cells—decreased digestion of fluorescently labelled gelatin and MMP‐9 activity were observed in melanoma cells with diminished level of this protein. Similar effect was observed by Sun et al who showed that MiR‐329 caused down‐regulation of MET expression what led to decreased mRNA level of MMP‐7 and MMP‐9 and thus reduced cellular migration and invasiveness of lung cancer cells.…”
Section: Discussionsupporting
confidence: 82%
“…5,19,38,39,40,41 miRNAs may act as tumor suppressor and are usually downregulated in cancer tissue. For example, the miR-206 is downregulated in NSCLC and suppresses the proliferation of A549 and SK-MES-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,13,14 miRNAs have been involved in various of biological processes corrected with tumor initiation, development and progression, including tumor cell growth and metastasis, cell identity, senescence, apoptosis, and stem cell maintenance. 15,16,17,18,19 Cui and his colleagues reported that miR-224 promoted tumor progression in non–small-cell lung cancer partially antagonist functions of SMAD4 and TNFAIP1. 20 And another miRNA, namely miR-31, predicted the presence of lymph node metastases and survival in patients with lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, miRNAs are described as a kind of emerging clinical, diagnostic, and prognostic biomarker, as well as treatment approach 9, 10. Sun et al 11, 12, 13, 14, 15. have explored the association between miRNAs and non-small cell lung cancer (NSCLC), revealing miR-139-5p, miR-187, miR-206, miR-326, and miR-329 were downregulated in lung cancer cell lines and tissues and played tumor-suppressive roles by targeting specific 3′ UTR of mRNAs for several oncogenes.…”
Section: Main Textmentioning
confidence: 99%